2016
DOI: 10.1371/journal.pone.0168507
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Tree Height Distribution Based on Mixed Effects Univariate Diffusion Processes

Abstract: The aim of this paper is twofold: to introduce the mathematics of stochastic differential equations (SDEs) for forest dynamics modeling and to describe how such a model can be applied to aid our understanding of tree height distribution corresponding to a given diameter using the large dataset provided by the Lithuanian National Forest Inventory (LNFI). Tree height-diameter dynamics was examined with Ornstein-Uhlenbeck family mixed effects SDEs. Dynamics of a tree height, volume and their coefficients of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In the previous study [17], calibration relies on the mean trend Equation 9to predict the random effects in relation to fixed effects parametersθ m estimated by approximated maximum likelihood procedure (see Equations (41) and (42)). Both alternative techniques deal adequately with random effects calibration, whose are essential for analyzing large observed datasets.…”
Section: Random Effects Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study [17], calibration relies on the mean trend Equation 9to predict the random effects in relation to fixed effects parametersθ m estimated by approximated maximum likelihood procedure (see Equations (41) and (42)). Both alternative techniques deal adequately with random effects calibration, whose are essential for analyzing large observed datasets.…”
Section: Random Effects Calibrationmentioning
confidence: 99%
“…In order to overcome these disadvantages, the multivariate stochastic differential equations have recently gained a lot of attention. Stochastic differential equations are often used in the modeling of population dynamic [10][11][12], tumor growth [13], chemical reaction networks [14], environmental pollution [15,16], forest growth and yield [17]. The deterministic differential equation carries its solution, which is completely determined in the value sense by knowledge of boundary and initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Diameter and height dynamics via an average stand age as a bivariate stochastic process were modeled using fixed effects reducible SDEs [25]. More recently, mixed effects univariate SDE models have provided the means to quantify and distinguish additional sources of variability in an observed dataset [26]. In addition to the inter-individual variability, multivariate SDE models also consider the covariance structure between size components [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The Gompertz, Verhulst, Bertalanffy, and Maltussian type SDEs were used to model the total tree height over age [10] and diameter [11,12], to model the stem taper [13], and to model tree crown width over diameter [14]. They found that the SDE models provided much more accurate predictions of individual tree height and crown width compared to nonlinear regression models.…”
Section: Introductionmentioning
confidence: 99%